2011
DOI: 10.1055/s-0030-1269838
|View full text |Cite
|
Sign up to set email alerts
|

Patientensicherheitsindikatoren zur Arzneimitteltherapiesicherheit (AMTS-PSI): Internationaler Status, Übertragbarkeit und Validierung

Abstract: An AMTS-PSI-set was identified by a systematic review and recognised as valid for transferring it to the pharmacotherapy care of the German Health Care System by the "qualify-instrument". These 14 AMTS-PSI are mainly characterised by their relevance. Before using these indicators in practice, their further operationalisation seems necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The majority of the included studies originated from Germany (18/30 studies, 60%), followed by the USA (5), Australia (3), UK (2), Ireland (1) and Switzerland (1). Study designs (by decreasing order of evidence 28 ) were: 1 systematic review, 29 4 randomised controlled trials (RCT), 30–33 10 cohort studies, 34–43 7 cross-sectional studies, 5 44–49 2 qualitative evaluations, 4 50 4 surveys 51–54 and 2 reports. 55 56 Thirteen studies reported statistically significant results with the use of medication charts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the included studies originated from Germany (18/30 studies, 60%), followed by the USA (5), Australia (3), UK (2), Ireland (1) and Switzerland (1). Study designs (by decreasing order of evidence 28 ) were: 1 systematic review, 29 4 randomised controlled trials (RCT), 30–33 10 cohort studies, 34–43 7 cross-sectional studies, 5 44–49 2 qualitative evaluations, 4 50 4 surveys 51–54 and 2 reports. 55 56 Thirteen studies reported statistically significant results with the use of medication charts.…”
Section: Resultsmentioning
confidence: 99%
“…In the systematic review on safety-relevant indicators, a medication chart was identified as one out of 14 parameters to ensure medication safety as well as patient safety. 29 Over 80% of the patients (N=138) in an RCT indicated that the medication chart helped them ‘avoid making mistakes with medications’ that were further described as medication intake errors such as wrong time, wrong pill or missed pill. 30 Another study measured a significant reduction of missed or delayed medication doses per patient after the implementation of a medication chart at discharge from hospital to nursing homes (from 37/202; 18.3% missed or delayed doses, to 6/226; 2.7%, p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons extend to the identi cation and resolution of drug-related problems including also inadequate communication across care interfaces. For this purpose, informing the patients on their medication by listing it on a (standardized) medication plan (MP) with all relevant information may prevent many of those problems and MPs have been identi ed as a relevant factor for patient safety [ 2 , 3 ]. Additionally, it was shown that further information, especially on handling, helps to improve patient knowledge about medication compared to control groups with only standard information [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Der fehlende Überblick über die Gesamtmedikation des Patienten ist eine häufige Ursache von Medikationsfehlern [3]; kritische Situationen wie Interaktionen oder unerwünschte Arzneimittelwirkungen werden dadurch häufig nicht rechtzeitig erkannt. Eine Lösung hierfür ist die interprofessionelle Nutzung eines Medikationsplans (MP) [4]. In Deutschland wurde im Rahmen der Aktionspläne zur Verbesserung der Arzneimitteltherapiesicherheit (AMTS) des Bundesministeriums für Gesundheit (BMG) ein Standard für einen solchen MP entwickelt, der sogenannte bundeseinheitliche Medikationsplan (BMP) [5].…”
Section: Introductionunclassified